The Biological Activity of Extraction of Protein Compound From Metapenaeus on Giardia Lamblia - Shatha Khudhaier Abbas (Journal of Global Pharma Technology, 2017)
The study includes the extraction of whole bodies of local shrimp from Shatt Al-Arab during Jun 2012 on Giardia lambia which collected sample from Ibn Al-Balady hospital in Baghdad from patients clinic. The result of study the extract caused all effect was killed of parasite on sixth day followed by shrimp extract and then shrimp extract and cyst continue to decline until it reached in seventh day and (WBC) in extractwas and in extract compare with control group and Flagel group , and the result found MLC in killed the parasite in seventh day.Keywords: Giardia lamblia, Metapenaeus, Red blood cells, White blood cells, Hemoglobin, Packed cell volume.